IMPLODING THE MEANING OF IDENTITY IN PHILIP ROTH’S THE HUMAN STAIN - Mukhopadhyay, Averi (Journal of Dharma, 2018)
The multi-ethnic, multi-lingual, multi-cultural and racially mixed nature of contemporary American society is accountable for a troubled history of ‘identity.’ Identities are shaped on the basis of race, ethnicity, language, class, and gender, all of which are still paramount and alive in the US. Identity has often demarcated between the ruler and the ruled, the oppressor and the oppressed, the white and the black, the male and the female, often subjecting the latter in the relationships to a prejudicial treatment and identifying it as the ‘other.’ The demarcation questions the fixed, coherent and stable nature of ‘identity’ based on monolithic categories, thereby, necessitating a redefinition of interpretive patterns and existing theories of identity. In Philip Roth’s The Human Stain, Coleman Silk is intent on keeping his disadvantaged African-American identity a secret from all, including his wife and their four children. He, for the most part of the book is seen as deconstructing and challenging his existing Negroid origin. His desire for purification and for freedom convinces him to pass as white. This paper studies the complexities of contemporary identity where individuals are caught hanging tantalizingly between the 'given' group identity and the 'chosen' self identity.